Peningkatan Kapabilitas Internal Audit Instansi Pemerintah - Dewi Kurniati Airlangga; Hilda Rossieta (Politeknik Ganesha Medan, 2023)
In implementing supervisory duties, internal auditors must have capabilities that consist of capacity, authority, and competency. The level of capability is measured using six elements of the Internal Audit Capability Model. This study aims to determine the efforts to strengthen the Inspectorate General of Ministry X in achieving level 4 capability of Government Internal Supervisory Apparatus. Internal audit capability level 4 is an excellent assurance of governance, risk, and control from the organization. Therefore, the role of internal auditor as a strategic counterpart is needed. Furthermore, obstacles and challenges were analyzed and evaluated for this Inspectorate General of Ministry X. The research used a qualitative method with a case study approach. Document reviews and interviews are used to collect the data. The results showed that several efforts had been made to improve internal audit capability based on BPKP Regulation No. 8 of 2021 concerning Capability Assessment of Government Internal Supervisory Apparatus. However, there is still an element of Internal Audit Capability Model at level 3 based on the self-assessment results, while others have not fully met the infrastructure for level 4. It is necessary to evaluate for three consecutive years and implement Enterprise Risk Management comprehensively. Thus internal auditor can utilize Enterprise Risk Management for its supervisory activities. The results of this study can also contribute to other institutions that are working to achieve internal audit capability level 4